The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/adma.201500098
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost Facile Fabrication of Flexible Transparent Copper Electrodes by Nanosecond Laser Ablation

Abstract: Low-cost Cu flexible transparent conducting electrodes (FTCEs) are fabricated by facile nanosecond laser ablation. The fabricated Cu FTCEs show excellent opto-electrical properties (transmittance: 83%, sheet resistance: 17.48 Ω sq(-1)) with outstanding mechanical durability. Successful demonstration of a touch-screen panel confirms the potential applicability of Cu FTCEs to the flexible optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 36 publications
4
100
1
Order By: Relevance
“…( d ) Φ TC values as a function of transmittance. For comparison, the Φ TC value of Ag mesh45, aligned Ag NW15, Ag nanomesh26, Cu flexible TCEs (FTCEs)46, reduced graphene oxide (RGO)/Au grids4, graphene/Ag grids47, AgCu alloy mesh48, and modified PEDOT:PSS6 are also shown.…”
Section: Figurementioning
confidence: 99%
“…( d ) Φ TC values as a function of transmittance. For comparison, the Φ TC value of Ag mesh45, aligned Ag NW15, Ag nanomesh26, Cu flexible TCEs (FTCEs)46, reduced graphene oxide (RGO)/Au grids4, graphene/Ag grids47, AgCu alloy mesh48, and modified PEDOT:PSS6 are also shown.…”
Section: Figurementioning
confidence: 99%
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the great challenge for transparent conductive plastic films is to sustain excellent mechanical durability and electrical continuity upon repeated bending or at high temperature processing 2 . Generally, indium tin oxide (ITO) has been widely used as transparent conductors due to its high transparency and low sheet resistance (over 80% and below 30 Ohm/sq) on a flexible substrate 7,8 , but the inherent brittleness of ITO usually causes cracks upon bending or folding 9,10 . Therefore, it is desirable to find a strong competitive replacement with excellent thermal stability that can be bent and even fully folded.…”
Section: Introductionmentioning
confidence: 99%